Enhancing the paracrine effects of adipose stem cells using nanofiber-based meshes prepared by light-welding for accelerating wound healing. (January 2023) - Liu, Na; Zhou, Ziyi; Ning, Xuchao; Zhang, Xiaopei; Guo, Qingxia; Guo, Mingxia; Wang, Yuanfei; Wu, Tong
Graphical abstract: Scheme 1. The purpose of this experiment was to investigate the effect of a series of nanofiber-based meshes prepared by electrospinning on the paracrine behavior of adipose stem cells (ADSCs). The scaffolds for cell culture included LNSG, MNSG, and SNSG. The best scaffold, SNSG, was selected, and ADSCs were loaded on the SNSG to be used in the rat skin wound healing model. Highlights: A series of nanofiber-based meshes were fabricated by electrospinning and light-welding technology to enhance the paracrine effects of ADSCs. The migration of fibroblasts and endothelial cells were significantly accelerated. The angiogenesis was also highly promoted. The production of type I collagen and the formation of CD31-positive blood vessels were observed in rat skin wound healing. Abstract: The interaction between electrospinning nanomaterials and stem cells to repair damaged tissue mainly focus on manipulating cell viability, proliferation, or paracrine by the materials and their specific topology. In particular, the paracrine products of stem cells influence the behavior of those repairable cells ( i.e., epidermal cells, fibroblasts, and endothelial cells) to speed up the repair progress. In this study, a series of nanofiber-based meshes were fabricated by electrospinning and light-welding technology to investigate their impacts on the paracrine behaviors of adipose stem cells (ADSCs) and their performance in accelerating wound healing. We found that the nanofiber-based meshes with varied grid sizes and modified with gelatin nanofibers could regulate the paracrine of ADSCs. As a result, the migration of fibroblasts and endothelial cells as well as angiogenesis was all influenced in vitro . In vivo investigation using rat skin wound healing models also indicated that the nanofiber-based meshes could accelerate wound healing rate, increase the thickness of the regenerated epidermis, and promote type I collagen production and CD31-positive vessel formation in the dermis layer. Taken together, such nanofiber-based meshes provide effective and promising alternatives to design tissue-repair scaffolds involving manipulating stem cell paracrine and wound closure.